The Effect of Work Facilities and Work Effectiveness on Public Satisfaction Through Service Quality at The Tungkal Ilir District Office, West Tanjung Jabung Regency - Jusmarni Jusmarni; M. Zahari; Fakhrul Rozi Yamali (Green Publisher, 2026)
Public satisfaction is a key indicator of successful public service delivery. Achieving this satisfaction is inseparable from the availability of work facilities and the effectiveness of staff, which can drive optimal service quality. This study aims to analyze the influence of work facilities and work effectiveness on public satisfaction through service quality at the Tungkal Ilir District Office, West Tanjung Jabung Regency. This study used a quantitative approach with a survey method. The study population consisted of 396 service recipients, with a sample size of 123 respondents determined using the Slovin formula with a 7.5% margin of error. Data collection was conducted using a questionnaire with a five-level Likert scale. Data analysis used path analysis based on Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The results showed that work facilities and work effectiveness had a positive and significant effect on service quality. Furthermore, service quality had a positive and significant effect on public satisfaction. The results of the mediation test indicated that service quality was able to mediate the influence of work facilities and work effectiveness on public satisfaction. These findings confirm that improvements in work facilities and the effectiveness of civil servants need to be continuously optimized to improve service quality and public satisfaction.